(untitled) (Circe de clásicos y modernos, 2018)
In this paper an interpretation of the use of expressions as ‘inspiration’ and ‘enthusiasm’ in the context of the platonic poetology is suggested. This interpretation tries to clarify the apparent contradiction between the platonic statement that (1) the poet had no knowledge and (2) poetry possibly can offer true contents. So the chance of decoding the figurative use of these expressions through the epistemological notion coined by Plato of ‘true belief’ is investigated.